Evaluasi Penggunaan Obat Pada Pasien Gastroesophageal Reflux Disease (GERD) Rawat Jalan Di Rumah Sakit Umum Purbowangi Gombong Periode Tahun 2019-2020 - Ani Meiningsih; Tri Cahyani Widiastuti; Husnul Khuluq (Universitas Borneo Lestari, 2022)
Background: Gastroesophageal Reflux Disease (GERD) is a digestive tract disease that attacks the stomach, which is caused by the return of contents from the stomach into the esophagus, with various signs and symptoms such us Heartburn and Regurgitation. This disease is often considered a normal disease, but this disease can cause recurrence to death, where if this is left it will cause severity and eventually stomach acid will be injured and ulcers occur which will cause vomiting of blood. One of the treatments for this disease is by offering H2RA drugs, Antacids, Sucralfat and PPIs that are appropriate to ensure the quality and effectiveness of Gastroesophageal Reflux Disease (GERD) therapy which includes the right indication, right patient, right drug and right dose (4 T). Research methods: Non-experimental research with retrospective data collective, total sampling technique and analyzed descriptively. Results: In this study, 81 cases of Gastroesophageal Reflux Disease (GERD) were obtained. the resulting data was then compared with Koda Kimble 2013. Get results 100% right on the indication, 95% right fot the patient, 85% right on the drug and 33% right on the dose at Purbowangi Gombong General Hospital for the period 2019-2020. Conclusion : Evaluation of the use of drugs to treat Gastroesophageal Reflux Disease (GERD) it is known that it is correct right on the indication, right fot the patient, right on the drug and right on the dose in accordance with the Koda Kimble 2013.